2013
DOI: 10.1016/j.redox.2013.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective effect of the antioxidant curcumin: Recent findings

Abstract: For years, there have been studies based on the use of natural compounds plant-derived as potential therapeutic agents for various diseases in humans. Curcumin is a phenolic compound extracted from Curcuma longa rhizome commonly used in Asia as a spice, pigment and additive. In traditional medicine of India and China, curcumin is considered as a therapeutic agent used in several foods. Numerous studies have shown that curcumin has broad biological functions particularly antioxidant and antiinflammatory. In fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
327
2
13

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 483 publications
(354 citation statements)
references
References 79 publications
12
327
2
13
Order By: Relevance
“…ATP, adenosine triphosphate; Ca2+, calcium cation; CI, NADH:ubiquinone oxidoreductase; CII, succinate dehydrogenase; CIII, coenzyme Q: cytochrome c-oxidoreductase; CIV, cytochrome c oxidase; Cyt c, cytochrome c; GSH, glutathione; MPT, permeability transition pore; ROS, reactive oxygen species; D m, mitochondrial membrane potential. mustard, cheese, cereals, soups, ice cream and yogurt (Shishodia et al 2007;Trujillo et al 2013;Waseem et al 2014).…”
Section: Curcuminmentioning
confidence: 99%
“…ATP, adenosine triphosphate; Ca2+, calcium cation; CI, NADH:ubiquinone oxidoreductase; CII, succinate dehydrogenase; CIII, coenzyme Q: cytochrome c-oxidoreductase; CIV, cytochrome c oxidase; Cyt c, cytochrome c; GSH, glutathione; MPT, permeability transition pore; ROS, reactive oxygen species; D m, mitochondrial membrane potential. mustard, cheese, cereals, soups, ice cream and yogurt (Shishodia et al 2007;Trujillo et al 2013;Waseem et al 2014).…”
Section: Curcuminmentioning
confidence: 99%
“…Also, it attenuated oxidative stress by reducing levels of nicotinamide adenine dinucleotide phosphate (NADPH) [20]. Also according to some other studies, it was suggested that, the nephroprotective effect of curcumin was related to the downregulation of the profibrotic cytokines vascular endothelial growth factor (VEGF), TGF-ß, CTGF and osteopontin as in extracellular matrix proteins fibronectin and collagen IV [20].…”
Section: Role Of Curcumin In Nephrotoxicitymentioning
confidence: 97%
“…The phenolic groups in the structure of curcumin can explain its properties to react with reactive oxygen species (ROS) and reactive nitrogen species (RNS) and may probably explain one of the mechanisms through which it protects the epithelial cells of renal tubules from oxidative damage induced by H 2 O 2 [19]. The indirect antioxidant activity of curcumin is explained by its ability to induce the expression of cytoprotective proteins such as superoxide dismutase (SOD), catalase (CAT), glutathione reductase (GR), glutathione peroxidase (GPx), heme oxygenase 1 (HO-1), glutathione-S-transferase (GST), NAD(P)H: quinone oxidoreductase 1 (NQO1) and γ-glutamylcysteine ligase (γGCL) [20].…”
Section: Anti-oxidant and Anti Oxidative Stress Activity Of Curcuminmentioning
confidence: 99%
See 2 more Smart Citations